PENERAPAN PERCEIVED STRESS SCALE DALAM PSYCHOLOGICAL SELF-ASSESSMENT UNTUK MENGUKUR TINGKAT STRES MENGGUNAKAN METODE K-NEAREST NEIGHBORS - Nadia Rizatul Riski; Safwandi Safwandi; Said Fadlan Anshari (LPPM Universitas Abdurrab, 2025)
Stress is a common psychological issue experienced by university students, particularly in high-pressure academic environments such as engineering faculties. This study aims to develop a digital self-assessment system to measure student stress levels using the Perceived Stress Scale (PSS-10) and the K-Nearest Neighbors (KNN) classification method. Data were collected from 100 respondents from the Faculty of Engineering at Universitas Malikussaleh. The system classifies stress levels into three categories: mild, moderate, and severe. Testing was conducted using 5-fold cross-validation. The evaluation results show an average accuracy of 83%, weighted precision of 79.18%, weighted recall of 84.70%, and weighted F1-score of 80.10%. These findings indicate that the system is capable of providing fairly accurate stress classification and can serve as a useful tool for independent stress detection.